Cognitive Screening Instruments : A Practical Approach - Larner, A. J. (Springer International Publishing : Imprint: Springer, 2017)
This revised and updated second edition provides a practical and structured overview of some of the most commonly used and easily available cognitive screening instruments applicable in the outpatient clinic and bedside setting. It now includes additional chapters on AD8 and also methodological aspects of systematic cognitive screening instrument assessment from the Cochrane Dementia and Cognitive Improvement Group. Expert authors from around the world equip the reader with clear instructions on the usage of each screening instrument, its strengths and weaknesses, and the time required for administration. Rules on scoring are also provided, such as how to correct for variations in the patient's age or education, and suggested cut-off scores. Cognitive Screening Instruments: A Practical Approach, Second Edition is aimed at both clinicians and professionals in disciplines allied to medicine who are called upon to assess patients with possible cognitive disorders, including neurologists, old age psychiatrists, neuropsychologists, primary care physicians, dementia support workers, and members of memory assessment teams.